2019
DOI: 10.1021/acscatal.9b03045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism and Kinetics of Isobutene Formation from Ethanol and Acetone over ZnxZryOz

Abstract: Isobutene is a specialty chemical used in the production of fuel additives, polymers, and other high-value products. While normally produced by steam cracking of petroleum naphtha, there is increasing interest in identifying routes to synthesizing isobutene from biomass-derived compounds, such as ethanol and acetone. Recent work has shown that zinc−zirconium mixed oxides are effective and selective catalysts for producing isobutene from ethanol. However, the reaction pathway, the roles of acidic and basic site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 73 publications
(143 reference statements)
0
35
1
Order By: Relevance
“…[ 100 ] Bell recently investigated the mechanism of this reaction and found that acetic acid is an intermediate in the ethanol to isobutene route, as well as a byproduct that is readily recycled ( Figure ). [ 101 ] The Wang group has patented both approaches and the subsequent conversion of isobutene to MAA. [ 102 ]…”
Section: Production Of Biobased Acrylates and Analogsmentioning
confidence: 99%
“…[ 100 ] Bell recently investigated the mechanism of this reaction and found that acetic acid is an intermediate in the ethanol to isobutene route, as well as a byproduct that is readily recycled ( Figure ). [ 101 ] The Wang group has patented both approaches and the subsequent conversion of isobutene to MAA. [ 102 ]…”
Section: Production Of Biobased Acrylates and Analogsmentioning
confidence: 99%
“…Eze et al [15] and Alptekin and Canalci [16] found that water, which can be produced from the mixing process of a strong alkaline catalyst and methanol, can cause a saponification phenomenon once it is mixed with the raw oil prior to transesterification. Therefore, the formation of OH − radicals from the dissociation of water might have promoted the ensuing transesterification reaction of the raw oil with an adequate amount of water added [17]. Moreover, the water content would have facilitated the hydrolysis of the raw oil's fatty acids [18], leading to the production of free fatty acids and thus increasing the acid value [19].…”
Section: Acid Value Of the Biodieselmentioning
confidence: 99%
“…Acetone conversion to isobutene takes place predominantly on the Lewis acid sites. 52 In the first stage, aldol condensation between an acetone molecule adsorbed on the Lewis site and an acetone molecule from the gaseous phase take place to produce a diacetone alcohol. The next pathway consists of a ⊎-scission reaction of diacetone alcohol, with formation of isobutene and acetic acid molecules.…”
Section: Acetic Acid Ketonizationmentioning
confidence: 99%